2022
DOI: 10.3390/molecules27154933
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Core Microbiota Based on Characteristic Flavor Compounds in Different Fermentation Phases of Sufu

Abstract: Sufu, a Chinese traditional fermented soybean product, has a characteristic foul smell but a pleasant taste. We determined the core functional microbiota and their metabolic mechanisms during sufu fermentation by examining relationships among bacteria, characteristic flavor compounds, and physicochemical factors. Flavor compounds in sufu were detected through headspace solid-phase microextraction coupled with gas chromatography–mass spectrometry, and the microbial community structure was determined through hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…(A) 2,5-Dioxopentanoate to 1,4-butanediol (Shepelin et al, 2018), and 1,4-butanediol to 4-hydroxy-3-keto-butyryl-CoA (Qian et al, 2023). (B) 2-Methylbutanal to 2-methylbutyric acid (Wu et al, 2022). (C) Hydroxytyrosol to acteoside (Li et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(A) 2,5-Dioxopentanoate to 1,4-butanediol (Shepelin et al, 2018), and 1,4-butanediol to 4-hydroxy-3-keto-butyryl-CoA (Qian et al, 2023). (B) 2-Methylbutanal to 2-methylbutyric acid (Wu et al, 2022). (C) Hydroxytyrosol to acteoside (Li et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…5B). In this occasion, a biochemical reaction (dihydrolipoyllysine-residue transferase) converting 2-methylbutanal into 2-methylbutyric acid was identified (Wu et al, 2022). Hydroxytyrosol, which is found in olive leaves and olive oil primarily in the form of oleuropein, is utilized for its anti-inflammatory, antioxidant, anticancer, antimicrobial, and antidiabetic properties (Arangia et al, 2023) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burkholderia‐Caballeronia‐Paraburkholderia accounts for about 0.1% of bacteria in the 0–5 days and during the mid‐fermentation stage, its proportion increases to 0.5%, accounting for 0.37% in the finished BLMJ. Burkholderia‐Caballeronia‐Paraburkholderia are dominant bacteria in a variety of fermented foods, such as fermented Dongcai, Sufu, Doubanjiang (Yang et al ., 2021; Wu et al ., 2022; Jiang et al ., 2023). A previous study has shown that Burkholderia–Caballeronia–Paraburkholderia play an important role in the flavour formation of fermented Sufu at the early fermentation stage (Wu et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Burkholderia‐Caballeronia‐Paraburkholderia are dominant bacteria in a variety of fermented foods, such as fermented Dongcai, Sufu, Doubanjiang (Yang et al ., 2021; Wu et al ., 2022; Jiang et al ., 2023). A previous study has shown that Burkholderia–Caballeronia–Paraburkholderia play an important role in the flavour formation of fermented Sufu at the early fermentation stage (Wu et al ., 2022). However, there have been few reports on how Burkholderia–Caballeronia–Paraburkholderia produce these flavour compounds, possibly due to its ability to produce lipase, which can decompose lipids and produce volatile compounds.…”
Section: Resultsmentioning
confidence: 99%